PENGARUH PENERAPAN MODEL PEMBELAJARAN INQUIRY TERHADAP KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK KELAS XI MIA SMAN 1 BATANG KAPAS - NISSA FISKA (Departemen Matematika, 2018)
Mathematical reasoning ability is one of the abilities that are expected to increase and develop in mathematics learning, but in reality students' mathematical reasoning abilities are not optimal. The application of inquiry learning model is one effort that can be done to improve students' mathematical reasoning abilities. This study aims to uncover and describe whether students 'mathematical reasoning abilities who learn to use inquiry learning models are better than students' mathematical reasoning abilities who learn to use direct learning models. The type of this research used is quasi experiment with the research design of The Static Group Design. Based on the results of the final test data analysis, it was concluded that the mathematical reasoning abilities of students who learn with inquiry learning models are better than the mathematical reasoning abilities of students who learn with direct learning models.Keywords – Inquiry Learning Model, Mathematics Learning, Mathematical Reasoning Ability.